Is chemotherapy necessary for patients with molar pregnancy and human chorionic gonadotropin serum levels raised but falling at 6 months after uterine evacuation? - Braga, Antonio; Torres, Berenice; Burla, Marcelo; Maesta, Izildinha [UNESP]; Sun, Sue Yazaki; Lin, Lawrence; Madi, Jose Mauro; Uberti, Elza; Viggiano, Mauricio; Elias, Kevin M.; Berkowitz, Ross S. (Elsevier B.V., 2016)
Objective. To compare the outcomes of Brazilian patients with molar pregnancy who continue human chorionic gonadotropin (hCG) surveillance with those treated with chemotherapy when hCG was still positive, but falling at 6 months after uterine evacuation. Methods. Retrospective chart review of 12,526 patients with hydatidiform mole treated at one of nine Brazilian reference centers from January 1990 to May 2016. Results. At 6 months from uterine evacuation', 96 (0.8%) patients had hCG levels raised but falling. In 15/96 (15.6%) patients, chemotherapy was initiated immediately per FIGO 2000 criteria, while 81/96 (84.4%) patients were managed expectantly. Among the latter, 65/81 (80.2%) achieved spontaneous remission and 16 (19.8%) developed postmolar gestational trophoblastic neoplasia (GTN). Patients who received chemotherapy following expectant management required more time for remission (11 versus 8 months; p = 0.001), had a greater interval between uterine evacuation and initiating chemotherapy (8 versus 6 months; p < 0.001), and presented with a median WHO/FIGO risk score higher than women treated according to FIGO 2000 criteria (4 versus 2, p = 0.04), but there were no significant differences in the need for multiagent treatment regimens (1/15 versus 3/16 patients, p = 0.60). None of the women relapsed, and no deaths occurred in either group. Conclusion. In order to avoid unnecessary exposure of women to chemotherapy, we no longer follow the FIGO 2000 recommendation to treat all patients with molar pregnancy and hCG raised but falling at 6 months after evacuation. Instead, we pursue close hormonal and radiological surveillance as the best strategy for these patients. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Molar pregnancy; Human chorionic gonadotropin; Chemotherapy